ORGANIZATIONAL FOUNDATIONS OF THE DEVELOPMENT OF A HEALTHY AND CREATIVE ENVIRONMENT IN THE MANAGERIAL ACTIVITIES OF LEADERS - Mavlanova , Zilola Torakulovna (Innovative Development in Educational Activities, 2024)
Young specialists with the above qualities are trusted in the selection of personnel for leadership positions, and special attention is paid to finding capable, talented and talented young people for management activities, regular work with them, training and professional development.